Analisis Makna Konotatif Dalam Podcast Bocor Alus Episode Manuver Jokowi Jelang Lengser Pada Kanal Youtube Tempodotco - Fenny Anita; Neni Triana (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the connotative meanings found in the Bocor Alus podcast episode “Manuver Jokowi Jelang Lengser” on the Tempodotco YouTube channel, to describe their forms, and to explain their functions in constructing digital political narratives. This research employed a descriptive qualitative approach based on Geoffrey Leech’s theory of connotative meaning. The data consisted of utterances containing connotative meanings collected through listening, note-taking, data reduction, classification, and semantic interpretation. The findings revealed 18 utterances containing connotative meanings classified into four categories: political strategy, power transition, political legitimacy, and evaluative expressions toward political actors. Political strategy was identified as the dominant category. The findings indicate that connotative meaning functions as evaluative, constructive, and rhetorical devices in shaping digital political framing. This study confirms that language in political podcasts functions not only as an informational medium but also as an instrument for constructing political reality that influences audience interpretation.